KADAR KALSIUM DARAH ITIK MAGELANG (Anas javanica) BETINA DEWASA PADA PERIODE TIDAK BERTELUR DAN BERTELUR - , SEPTIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this study was to find out the level of calcium in blood serum between non laying and laying Magelang ducks. Eight clinically healthy Magelang ducks (4 non laying and 4 laying ducks) were used in this study. Blood samples were collected through brachial vein. Obtained samples were centrifuged for 10 minutes at 3266 rpm. Calcium serum analyzed using Beckman counter method. The data were analyzed by t-Test. The results showed that the mean of calcium serum ducks of non laying ducks was 11.12 Â± 0.46 mg/dl, while the calcium serum level of laying ducks was significantly at a higher level to 23.4 Â± 0.73 mg/dl (P<0.05). Based on the results, it could be concluded that blood calcium level of ducks was influenced by reproduction status. Keywords : Magelang duck, calcium